Synthesis of Mono‐, Bis‐ and Tris(pentafluoroethyl)tin Derivatives, (C2F5)4−nSnXn (X=Ph, Me, Cl, Br, Cp; n=1–3). Issue 34 (24th May 2017) - Klösener, Johannes; Wiesemann, Markus; Niemann, Mark; Neumann, Beate; Stammler, Hans‐Georg; Hoge, Berthold
Abstract: For (pentafluoroethyl)phenylstannanes, (C2 F5 )4− n SnPh n ( n =1–3), and dimethylbis(pentafluoroethyl)stannane, (C2 F5 )2 SnMe2, a high yield synthesis was developed by the use of LiC2 F5 as a C2 F5 transfer reagent. The treatment of these products with gaseous hydrogen chloride or hydrogen bromide afforded (C2 F5 )4− n SnX n (X=Cl, Br; n =1–3) in good yields. The (pentafluoroethyl)stannanes were fully characterized by 1 H, 13 C, 19 F and 119 Sn NMR, IR spectroscopy and mass spectrometry. The treatment of the (pentafluoroethyl)tin halides (C2 F5 )4− n SnX n with 1, 10‐phenanthroline (phen) led to the formation of the corresponding octahedrally coordinated complexes [(C2 F5 )4− n SnX n (phen)], the structures of which were elucidated by X‐ray diffraction analyses. The bromostannane (C2 F5 )3 SnBr reacted with sodium cyclopentadienide to give the ( η 1 ‐cyclopentadienyl)tris(pentafluoroethyl)stannane, (C2 F5 )3 SnCp, for which single‐crystal X‐ray diffraction analysis could be performed. The coupling constants 1 J ( 119 Sn, 13 C) and 2 J ( 119 Sn, 19 F) of all new stannanes are strongly correlated and sensitive to the substitution pattern at the tin atom. For both coupling constants a negative sign could be assigned. Abstract : Some‐tin special : We present a convenient protocol for the high yield synthesis of (pentafluoroethyl)stannanes ( n =1–3) by using LiC2 F5 . (Pentafluoroethyl)phenylstannanes are functionalized by gaseous hydrogen halides HX (X=Cl, Br) to give (pentafluoroethyl)tin halides. Their corresponding 1, 10‐phenanthroline (phen) complexes were structurally characterized by X‐ray diffraction analysis.